Cytotoxicity of Euphorbia macroclada on MDA-MB-468Breast CancerCell Line: Cytotoxicity of Euphorbia macroclada - Hojjat Sadeghi-Aliabadi,; Seyed Ebrahim Sajjadi,; Marziyeh Khodamoradi, (Iranian Journal of Pharmaceutical Sciences, 2009)
It has been reported that different species of Euphorbia(Euphorbiaceae) have antitumor activity. Some reports also show that these plants have potential cytotoxic effect against different cell lines. In a program to screen the cytotoxicity of Iranian native plants, Euphorbia macrocladaBoiss. was collected, identified, and the cytotoxic activity of dichloromethane, ethylacetate, methanol extracts, and the plant latex were determined against MDA-MB-468 cell line. Different concentration of extracts and latex were added to 24 h cultured cells and then incubated for 72 h under specific condition (37 °C, 5% CO2). Cell survival was evaluated using MTT assay. The results of this study indicated that, dichloromethane and ethylacetate extracts had cytotoxic effects on cell line, while the methanol extract and latex were not cytotoxic at the tested concentrations. The data from this investigation suggest that the nonpolar extracts of E. macrocladapossess higher cytotoxic activity.